FEATURES OF THE FUNCTIONING OF THE NATIONAL LABOR MARKET IN CONDITIONS OF MILITARY THREAT AND INTERNAL POPULATION DISPLACEMENT - Akimova, Liudmyla; Urchik, Gаlina (Social Economics, 2024)
The article presents a comprehensive study of the peculiarities of the functioning of the Ukrainian labour market in the context of modern challenges. The objective is to identify existing problems and transform the state policy in the labour market. The study was conducted based on data from the State Employment Service, the online job search portal Work.ua, and various sociological surveys of labour market participants and experts. The results of the analysis demonstrate that the Ukrainian labour market has undergone significant transformations during the war compared to peacetime. These include: 1) A notable decrease in the number of registered unemployed individuals. 2) A reduction in the proportion of unemployed individuals receiving unemployment benefits. 3) A sharp decline in the number of vacant jobs and employers informing the State Employment Service (SES) about available vacancies. 4) A high burden on vacant jobs. It can be posited that there was a considerable surplus of labour and considerable tension in the registered labour market during the war.According to the online job search resource Work.ua, the following trends have been identified in the general labour market of Ukraine: ) A «shock» state of the general labour market in 2022, with a gradual stabilisation in 2023. 2) The professional structure of labour demand in the most popular occupations did not change significantly during the war. The most popular occupations in the labour market are sales managers and sales consultants, accountants, and drivers. 3) A decrease in labour demand during the war occurred in several occupations, but the most significant decrease in labour demand occurred in the IT sector. In the majority of western regions, the ratio between professions with an increase or decrease in the number of vacancies favoured the former. In contrast, in the vast majority of eastern and central regions of Ukraine, the balance of changes in the number of vacancies is negative. Furthermore, in the face of threats to life and health, there is an increase in the supply of remote work. It can be stated that the main problems faced by employers when hiring employees are a lack of candidates for positions and an insufficiently qualified applicant pool. In this paper, we prove that the main problems of job seekers in the current conditions are unsatisfactory remuneration, a reduction in the scope of labour application, and age discrimination in the labour market. According to a survey of experts